A descriptive-contrastive analysis of English and Gaddang consonants and vowels - Bibat, Patricia (Belisario) 1925- (1967)
This study identifies the problems of the Gaddang speaker in learning the English consonant and vowel sounds. The objective is attained through a comparison made on the phonemes, allophones and distribution of the sounds of both the English and the Gaddang languages.
Thesis (M.A.T. English)--University of the Philippines, Diliman.
Keywords: Gaddang language -- Phonemics; English language -- Phonemics